Patrocínio empresarial e incentivos fiscais a cultura no Brasil: análise de uma experiência recente - Durand, José Carlos Garcia (1997)
The article examines the implantation of fiscal incentives for culture in Brazil from 1986 to 1995, in the federal, state and municipal leveis. The analysis is based on cultural authorities survey and shows the main challenges to the cultural policy modernization in Brazil. It also considers the main features of the incentive laws as ways to avoid fiscal frauds, describes advantages of these laws to the government, community and companies. Besides that, the article provides some quantitative information and analyses the results obtained until 1995.